Influence of Foliar Application of Growth Regulators on Vegetative Growth and Flowering Of Chrysanthemum (Bangladesh Journal of Agricultural Research, 2023)
The pot experiment was conducted at the Floriculture field of Horticulture Research Centre (HRC), Bangladesh Agricultural Research Institute (BARI), Gazipur during August 2020 to May 2021 to evaluate the foliar spray of gibberellic acid (GA3), benzyl adenine (BA) and naphthalene acetic acid (NAA) on growth and flowering traits of chrysanthemum (Chrysanthemum morifolium). The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Four weeks old seedlings of chrysanthemum genotype CM-019 (flower class: Pompon and flower colour: Orange yellow) were transplanted in pot keeping under natural sunlight. The aqueous solution of GA3, BA and NAA @ 100 and 200 ppm of each were sprayed on the flower plants at monthly interval starting after one month of transplantation of seedlings along with control (water). The results revealed that vegetative growth and flowering parameters were significantly influenced by plant growth regulators. Maximum number of leaves per plant (50.0) and leaf area per plant (7.5 cm2) were recorded from the spraying of BA @ 100 ppm closely followed by BA @ 200 ppm (48.0 and 7.0 cm2/plant) and GA3 @ 100 ppm only for number of leaves (47.0/plant). Spraying of GA3 @ 100 ppm produced the tallest plant (70.0 cm) and the highest plant spread (23.0 cm). Number of flowers (26.0/plant), flower size (7.8 cm), average weight of stalk (37.0 g) and vase life (15.0 days) were also found maximum from the application of GA3 @ 100 ppm, closely followed by GA3 @ 200 ppm (23.5/plant, 7.2 cm, 36.0 g, 14.0 days) and NAA @ 100 ppm (18.5/plant, 7.0 cm, 36.0 g, 13.0 days) and irrespective of concentrations, BA failed to improve these characters. GA3 @ 100 ppm recorded maximum length of stalk (37.5 cm) and rachis (29.0 cm), which was identical with GA3 @ 200 ppm (34.6 cm and 25.0 cm), and BA @ 100 ppm gave the lowest length of stalk and rachis. GA3 also caused faster initiation of flowering, whereas NAA and BA delayed it. GA3 @ 100 ppm took the minimum days to flowering (50.0 days) was observed when plants were sprayed with GA3 @ 100 ppm whereas it was maximum (69 days) from BA @ 100 ppm treatment. It can be concluded that GA3 @ 100 ppm provided the best results for obtaining better vegetative growth of plants, maximum number of cut blooms with longer stalk as well as bigger flower size with prolonged vase life in chrysanthemum.Bangladesh J. Agril. Res. 47(1): 69-80, March 2022